Effects of exercise and bryostatin-1 on functional recovery and posttranslational modification in the perilesional cortex after cerebral infarction. Issue 5 (22nd March 2023) - Mizutani, Kenmei; Sonoda, Shigeru; Wakita, Hideaki; Takahashi, Yu
Abstract : Strokes can cause a variety of sequelae, such as paralysis, particularly in the early stages after stroke onset. Rehabilitation therapy atthis time often provides some degree of paralysis recovery. Neuroplasticity in the peri-infarcted cerebral cortex induced by exercise training may contribute to recovery of paralysis after cerebral infarction. However, the molecular mechanism of this process remains unclear. This study focused on brain protein kinase C (PKC), which is speculated to be involved in neuroplasticity. We evaluated the functional recovery of cerebral infarction model rats, by using rotarod test after running wheel training and with/without administration of bryostatin, a PKC activator. In addition, the expression of phosphorylated and unphosphorylated PKC subtypes, glycogen synthase kinase 3β (GSK3β), and collapsin response-mediator proteins 2 (CRMP2) were analyzed by Western blotting. In the rotarod test, bryostatin administration alone had no effect on gait duration, but the combination of training and this drug significantly prolonged gait duration compared with training alone. In protein expression analysis, the combination of training and bryostatin significantly increased phosphorylation of PKCα and PKCε isoforms, increased phosphorylation of GSK3β, which acts downstream of PKC, and decreased phosphorylation of CRMP2. The effect of bryostatin in combination with training appears to be mediated via PKC phosphorylation, with effects on functional recovery occurring through the downstream regulation of GSK3β and CRMP2 phosphorylation.